Anion recognition properties of new upper-rim cobaltocenium calix[4]arene receptors - Beer, P; Hesek, D; Nam, K; Drew, M (1999)
New isomeric upper-rim bis(cobaltocenium)calix[4]arene receptors L1, L2 and a novel upper-rim cobaltocenium-bridged calix[4]arene derivative L3 have been synthesized and shown to selectively complex and electrochemically sense a variety of anionic guest species. Single-crystal X-ray structures of the chloride complexes of L1 and L3 emphasize the importance of hydrogen bonding and the topological nature of the upper-rim anion recognition site to the anion recognition process in the solid state. Proton NMR titration studies in deuterated DMSO solutions reveal these receptors form strong and remarkably selective complexes with MeCO2 and H2PO4- anions dependent upon the positioning of lower-rim tosyl substituents. Cyclic voltammetric investigations have demonstrated these receptors to electrochemically recognize carboxylate, H2PO4-, and Cl- anions.